2015
DOI: 10.1371/journal.pone.0123469
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Zinc Finger Protein-Specific Autoantibodies and Associated Linear B-Cell Epitopes in Colorectal Cancer

Abstract: Colorectal cancer is one of the most common cancers worldwide with almost 700,000 deaths every year. Detection of colorectal cancer at an early stage significantly improves patient survival. Cancer-specific autoantibodies found in sera of cancer patients can be used for pre-symptomatic detection of the disease. In this study we assess the zinc finger proteins ZNF346, ZNF638, ZNF700 and ZNF768 as capture antigens for the detection of autoantibodies in colorectal cancer. Sera from 96 patients with colorectal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…[ [135][136][137][138][139][140][141][142][143][144][145][146] VESICULAR TRAFFICKING AND CELL MIGRATION RHOD and RRAS2 are two of most important hub genes of GTPase family. The downexpression of RHOD could impair migration and proliferation of RPE cells.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…[ [135][136][137][138][139][140][141][142][143][144][145][146] VESICULAR TRAFFICKING AND CELL MIGRATION RHOD and RRAS2 are two of most important hub genes of GTPase family. The downexpression of RHOD could impair migration and proliferation of RPE cells.…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…Considering the clinical significance of methylation regulatory genes, Kaplan-Meier survival analysis was performed and the candidate key genes (NXPE4, REP15 and ZNF726), whose aberrant expression was linked to CRC prognosis, screened. ZNF proteins, including ZNF346, ZNF638, ZNF700 and ZNF768, are capture antigens for detecting autoantibodies in CRC (31). In addition, DNA methylation biomarkers of the ZNF gene family, combined with other genes, may be useful in the clinical setting for head and neck squamous cell carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…The following two predicted genes turn out to encode zinc finger proteins ZC4H2 and ZCCHC2. Zinc finger proteins have been widely reported to be abnormally functioning in colorectal cancer patients . As for its contribution to microsatellite instability, recent publications confirmed that such genes may involve in the regulation and maintenance of normal microsatellite status and patients with different MSI status may have different drug reactivity against zinc finger protein targeted drugs, implying the potential relationship between zinc finger proteins and colorectal cancer MSI status.…”
Section: Discussionmentioning
confidence: 99%